(untitled) (International Journal of Scientific Trends, 2024)
The article presents data on metabolic disorders in the body of cows excluded from milk as a consequence of etiological factors in calves dyspepsia and it’s prevention by adding sprouted verdure of the wheat, monocalcium phosphate and LPP-1 to the diet of cows.